2016
DOI: 10.3354/ab00649
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption and swimming behavior of juvenile Siberian sturgeon Acipenser baerii during stepped velocity tests

Abstract: Oxygen consumption rate (MO 2 ) and critical swimming speed (U crit ) of juvenile Siberian sturgeon Acipenser baerii were measured at 24°C using a step-wise velocity test in a flume-type respirometer. Swimming behavior was video-recorded before and after the swimming experiment in a respirometer and an open tank. The relationship between MO 2 and swimming speed (U) can be accurately described by a power function. The U crit of A. baerii was found to be 2.28 ± 0.09 body lengths (BL) s −1 or 0.51 ± 0.05 m s −1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The relationship between gill area, metabolic rate, and body mass in fish determines the typical growth pattern of the species (Archer et al, 2021). The daily average oxygen consumption rate and asphyxiation point of E. kishinouyei are higher than those of M. anguillicaudatus (Tsui et al, 2004), Epinephelus fuscoguttatus (Okomoda et al, 2020), and Acipenser baerii (Yuan et al, 2016), which are of similar size to E. kishinouyei. The vigorous aerobic metabolism and intolerance to hypoxia of E. kishinouyei may be associated with its long-term life in torrential environments.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between gill area, metabolic rate, and body mass in fish determines the typical growth pattern of the species (Archer et al, 2021). The daily average oxygen consumption rate and asphyxiation point of E. kishinouyei are higher than those of M. anguillicaudatus (Tsui et al, 2004), Epinephelus fuscoguttatus (Okomoda et al, 2020), and Acipenser baerii (Yuan et al, 2016), which are of similar size to E. kishinouyei. The vigorous aerobic metabolism and intolerance to hypoxia of E. kishinouyei may be associated with its long-term life in torrential environments.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of concentrations of various fish species, including sturgeon in the water areas of riverbed depressions, can be beneficial both from the point of view of shelter from predators in zones of increased turbidity (Wishingrad et al, 2014), and to save energy resources in the zones of low-velocity, which are formed in the presence of vertical vortex structures. It should be noted (Yuan et al, 2016;Duan et al, 2017) that individuals of the Siberian sturgeon have relatively high swimming performance and a relatively low coefficient of resistance due to the unique body shape, as well as a high ability to cope with oxygen deficiency, while individuals of this species, as well as individuals of sterlet, concentrate in riverbed depressions. Siberian sturgeon has a wide range of reaction rates, which allows it as a species to occupy vast territories and form life strategies inherent in populations inhabiting an environment characterized by different conditions (Ruban, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Also, one field study of migration of representatives of sturgeon in North America conducted with the help of acoustic equipment showed (McElroy et al, 2012) that the representatives of this family can still minimize energy consumption by using low-speed areas during migration. When studying the physiology of juvenile Siberian sturgeon (Yuan et al, 2016), as well as for individuals of Chinese sturgeon (Cai et al, 2014), it was found that their individuals, due to the metabolic characteristics of the organism, have a high ability to recover the energy spent on movement in the stream. This feature explains the pattern of increase in the share of the group Acipenseridae and Lotidae in the structure of ichthyofauna from the shore zone to midstream, from 10.2-17.1%, and for almost all size classes.…”
Section: Discussionmentioning
confidence: 99%